Expression of phosphoinositide-specific phospholipase C isoforms in human umbilical vein endothelial cells. Issue 10 (8th July 2011) - Lo Vasco, V R; Pacini, L; Di Raimo, T; D'arcangelo, D; Businaro, R
Abstract : Aims: The signalling system of phosphoinositides (PIs) is involved in a number of cell and tissue functions including membrane trafficking, ion channel activity, cell cycle, apoptosis, differentiation and cell and tissue polarity. Recently, a role in cell migration was hypothesised for PI and related molecules including the phosphoinositide-specific phospholipases C (PI-PLCs), main players in PI signalling. The expression of PI-PLCs is tissue-specific and evidence suggests that it varies under different conditions such as tumour progression or cell activation. In order to obtain a complete picture, the expression of all PI-PLC isoforms was analysed in human endothelial cells (EC). Methods: Using molecular biology methods (RT-PCR), the expression of PI-PLC isoforms was analysed in human umbilical vein endothelial cells (HUVEC), a widely used experimental model for human EC. Results: All the PI-PLC isoforms except PI-PLC β1, PI-PLC ɛ and PI-PLC ζ were expressed in HUVEC. Conclusions: The growing interest in the complex cascade of events occurring in angiogenesis will provide useful insights for therapeutic strategies. The expression of PI-PLC isoforms in HUVEC is a useful tool for further studies directed to understanding their role in angiogenesis. However, although HUVEC represent a widely used experimental model for human macrovascular EC, limitations remain in that they cannot fully represent the metabolic properties and interactions of the EC distributed in the entire organism.